Recent Advances in Strategies for Imaging Detection and Intervention of Cellular Senescence. (18th October 2022) - Li, Jili; Bi, Zhengyan; Wang, Linlin; Xia, Yinghao; Xie, Yuqi; Liu, Yanlan
Abstract: Cellular senescence is a stable cell cycle arrest state that can be triggered by a wide range of intrinsic or extrinsic stresses. Increased burden of senescent cells in various tissues is thought to contribute to aging and age‐related diseases. Thus, the detection and interventions of senescent cells are critical for longevity and treatment of disease. However, the highly heterogeneous feature of senescence makes it challenging for precise detection and selective clearance of senescent cells in different age‐related diseases. To address this issue, considerable efforts have been devoted to developing senescence‐targeting molecular theranostic strategies, based on the potential biomarkers of cellular senescence. Herein, we review recent advances in the field of anti‐senescence research and highlight the specific visualization and elimination of senescent cells. Additionally, the challenges in this emerging field are outlined. Abstract : Cellular senescence is emerging as a promising novel pharmaceutical target for prevention and treatment of a variety of age‐related disorders. However, its highly heterogeneous feature of senescence makes these goals difficult to achieve. This review will introduce recent progress in the anti‐senescence field, with special emphasis on the molecular probes for the imaging detection and selective intervention of cellular senescence.